Influence of lip posture and malocclusion type on incisor trauma - Soukaina Sahim; Amal El Aouame; Anas El kyaki; Farid El Quars (Elsevier, 2021)
Aim or Purpose: The aim of our study was to establish the relationship between the severity of the maxillary incisors' trauma, the type of malocclusion and the lip posture. Materials and Methods: This retrospective descriptive survey was conducted over a period of 3 months on 54 complete orthodontic files, at the dento-facial orthopedic department of the Dental Care Center of Casablanca (CCTD). The aesthetic analysis of RICKETTS was performed on pre-treatment lateral cephalograms. The data were collected through a questionnaire containing socio-demographic variables, clinical variables related to the trauma, type of dental malocclusion and lip posture. The Chi2 test was used to evaluate the different variables, the difference was found to be significant when p ⩽ 0.05. Results: According to our study, patients between 13 and 18 years of age appear to have an increased risk of trauma. Class II division 1 was the most frequent in the traumatized population (56%) and overjet greater than 3 mm was the most common (48%) with a highly significant difference. Lip incompetence was most frequent in the traumatized population (68%) and the reduced length of the upper lips was frequent (50%) with a significant difference. Conclusions: Dental trauma, especially in the anterior sector, is frequent in adolescent patients. Increased overjet and inadequate lip posture are two major risk factors for incisor trauma. Early orthodontic treatment might prevent dental trauma in these patients.